1995
DOI: 10.1016/0005-2728(94)00178-8
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of cytochrome c binding to membranes at physiological mitochondrial intermembrane space ionic strength

Abstract: We have shown that cytochrome c (cyt c) diffuses primarily in three dimensions in the intermembrane space (IMS) of intact mitochondria at physiological ionic strength (I). Recently, we found that a small percentage (11.2 +/- 2.1%) of endogenous cyt c remains bound to inner mitochondrial membranes (IMM) at high, physiological I (I = 150 mM), even after extensive washing with solutions at physiological I, overnight dialysis, changes in medium osmolarity, or further purification of IMM at high I using self-genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 62 publications
1
57
0
Order By: Relevance
“…Cytochrome c, which associates with the inner membrane, was stripped efficiently from the mitochondria under these conditions (Fig. 4A) as expected (17,18). In contrast, mitoNEET remained associated with the mitochondrial pellet as did other known integral membrane proteins such as BCL2 and voltage-dependent anion channel protein (Fig.…”
Section: Mitoneet Is An Integral Outer Membrane Protein Oriented Towamentioning
confidence: 71%
“…Cytochrome c, which associates with the inner membrane, was stripped efficiently from the mitochondria under these conditions (Fig. 4A) as expected (17,18). In contrast, mitoNEET remained associated with the mitochondrial pellet as did other known integral membrane proteins such as BCL2 and voltage-dependent anion channel protein (Fig.…”
Section: Mitoneet Is An Integral Outer Membrane Protein Oriented Towamentioning
confidence: 71%
“…Cytochrome c normally resides in the inter-membrane space of the mitochondria and is involved in energy transfer (38). However, a population of cytochrome c is released into the cytosol during apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cyt-c may function as a direct antioxidant in living cells (26). It is known that a large fraction of cyt-c does not participate in electron transport (27) and hence that cyt-c is present in excess in the mitochondrial intermembrane space. Electron microscopy studies have indicated that the release of cyt-c during apoptosis is a complete process, leading to a total depletion of cyt-c in affected mitochondria (28).…”
Section: Discussionmentioning
confidence: 99%